2017
DOI: 10.1002/14651858.cd009744.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Niacin for primary and secondary prevention of cardiovascular events

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 158 publications
3
45
0
Order By: Relevance
“…This translates into reductions in LDL-C and triglycerides whilst concomitantly raising HDL-C [ 103 , 104 ]. Despite the lack of cardiovascular efficacy when added to background statin therapy [ 105 ], its ubiquitous use continues worldwide [ 101 , 106 ]. Niacin often causes facial flushing as a side effect, which sometimes limits its use in general practice [ 107 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…This translates into reductions in LDL-C and triglycerides whilst concomitantly raising HDL-C [ 103 , 104 ]. Despite the lack of cardiovascular efficacy when added to background statin therapy [ 105 ], its ubiquitous use continues worldwide [ 101 , 106 ]. Niacin often causes facial flushing as a side effect, which sometimes limits its use in general practice [ 107 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…There is considerable evidence revealing that elevated level of plasma LDL-C is the independent risk factors for CVD [ 16 , 63 , 64 ]. Recently, other studies have also shown that elevated plasma TG levels also play an important role in the development of CVD [ 65 , 66 ]. Targeting on LDL-C and TG may effectively prevent the progress of CVD.…”
Section: The Function Of Angptl3mentioning
confidence: 99%
“…These findings are consistent with quantitative syntheses from previous meta-analyses. 46 , 47 By contrast, pooled estimates of the trials performed on the subgroup of patients without concurrent statin therapy indicated an association of niacin with 3 clinical outcomes, often reported as secondary end points: a reduced risk for acute coronary syndrome, stroke, and revascularization procedures.…”
Section: Discussionmentioning
confidence: 99%